Use of the curcumin analog BHMC in the treatment of endothelial dysfunction and related disorders - Israf Ali, Daud Ahmad; Tham, Chau Ling; Lajis, Mohd Nordin; Lam, Kok Wai (2012)
The present invention relates to an analog of curcumin, 2,6-bis-(4-hydroxyl-3-methoxybenzylidine)cyclohexanone (BHMC) or a pharmaceutically acceptable salt, solvate or derivative thereof, for use in treating, preventing or managing endothelial dysfunction and/or a disorder associated with endothelial dysfunction. Furthermore provided are methods of treating, preventing or managing endothelial dysfunction and/or a disorder associated with endothelial dysfunction using BHMC or a pharmaceutically acceptable salt, solvate or derivative thereof. The invention provides also a method for attenuating endothelial dysfunction in an endothelial cell and/or attenuating the hallmarks of endothelial dysfunction in an endothelial cell.